Tobacco Smoking: Risk to Develop Addiction, Chronic Obstructive Pulmonary Disease, and Lung Cancer - Santoro, Alessia; Tomino, Carlo; Prinzi, Giulia; Lamonaca, Palma; Cardaci, Vittorio; Fini, Massimo; Russo, Patrizia (Recent patents on anti-cancer drug discovery, 2019)
The morbidity and mortality associated with tobacco smoking is well established. Nicotine is the addictive component of tobacco. Nicotine, through the non-neuronal α7nicotinic receptor, induces cell proliferation, neo-angiogenesis, epithelial to mesenchymal transition, and inhibits drug-induced apoptosis. To understand the genetic, molecular and cellular biology of addiction, chronic obstructive pulmonary disease and lung cancer. The search for papers to be included in the review was performed during the months of July- September 2018 in the following databases: PubMed (http://www.ncbi.nlm.nih.gov), Scopus (http://www.scopus.com), EMBASE (http://www.elsevier.com/online-tools/embase), and ISI Web of Knowledge (http://apps.webofknowledge.com/). The following searching terms: "nicotine", "nicotinic receptor", and "addiction" or "COPD" or "lung cancer" were used. Patents were retrieved in clinicaltrials.gov (https://clinicaltrials.gov/). All papers written in English were evaluated. The reference list of retrieved articles was also reviewed to identify other eligible studies that were not indexed by the above-mentioned databases. New experimental data on the ability of nicotine to promote transformation of human bronchial epithelial cells, exposed for one hour to Benzo[a]pyrene-7,8-diol-9-10-epoxide, are reported. Nicotinic receptors variants and nicotinic receptors upregulation are involved in addiction, chronic obstructive pulmonary disease and/or lung cancer. Nicotine through α7nicotinic receptor upregulation induces complete bronchial epithelial cells transformation. Genetic studies highlight the involvement of nicotinic receptors variants in addiction, chronic obstructive pulmonary disease and/or lung cancer. A future important step will be to translate these genetic findings to clinical practice. Interventions able to help smoking cessation in nicotine dependence subjects, under patent, are reported.